Unveiling Electrical Problems Encountered by Women in Household Settings: A Skill Assessment - Rosales, Victor; Adelfa C. Silor,; Antonio M. Merca, (Journal of Technical Education and Training, 2025)
Electricity is essential in supporting household responsibilities, especially among women. This study assessed the home electrical problems encountered by women in Iligan City, Philippines, and evaluated their skill levels using the Conscious Competence Learning Model. A descriptive survey was conducted with 230 women from ten barangays. Most respondents were aged 29 and above (78.3%), married (77.0%), and belonged to low-income households (70.0% earning ₱5,000 or less monthly), with education clustered at the high school (27.0%) and elementary (19.6%) levels. Common issues included electric shocks (58.7%), power surges (53.5%), and unlicensed electrical work (46.1%), posing significant safety risks. Respondents identified themselves as "Consciously Unskilled" in addressing electrical concerns, signaling both awareness and willingness to learn. The study highlights the urgent need for TVET-aligned, gender-responsive training programs to build women's technical competence, enhance home safety, and support inclusive participation in skilled trades.